Меморијата на романот, романот како меморија - Марија Ѓорѓиева Димова (Филолошки факултет, Универзитет „Гоце Делчев“-Штип, 2020)
This text aims to elaborate the intertextual idea of the novel, as implied in Milan Kundera’s three books of essays The Art of the Novel, Testaments Betrayed and The Curtain. Composed in different time periods, the essays ‘write out’ the theory and the history of the novel from Kundera’s perspective as a novelist and a reader. Underscoring the awareness of the continuity the European novel inherited from Cervantes, the necessity of contextualizing the novel both in a creative and a receptive sense, Kundera’s essays favour intertextuality as a fundamental mechanism through which the novel creates its own genre memory: the intertextual immanence of the novel manifests itself as an awareness f its own tradition, its conventions and codes, of their observance and/or breach. In that sense, through an essayist interpretation of the novels, which form what Kundera calls „the pleiad of great novelists “ „a personal history of the novel “, the manner is confirmed in which every novel, through its intertextual markedness, is inscribed into the textual memory of the genre, while reorganizing and changing it, considering that it creates its own mnemonic space which has, in turn, been implied with its intertextuality.
The Memory of the Novel, the Novel as a Memory
Keywords: essay, novel, intertextuality, memory, genre autoreferentiality.